Locus of Control and the Preference for Agency - Marco Caliendo; Deborah A. Cobb-Clark; Juliana Silva Goncalves; Arne Uhlendorff (Institute of Labor Economics (IZA), 2023)
We conduct a laboratory experiment to study how locus of control operates through people's preferences and beliefs to influence their decisions. Using the principal-agent setting of the delegation game, we test four key channels that conceptually link locus of control to decision- making: (i) preference for agency; (ii) optimism and (iii) confidence regarding the return to effort; and (iv) illusion of control. Knowing the return and cost of stated effort, principals either retain or delegate the right to make an investment decision that generates payoffs for themselves and their agents. Extending the game to the context in which the return to stated effort is unknown allows us to explicitly study the relationship between locus of control and beliefs about the return to effort. We find that internal locus of control is linked to the preference for agency, an effect that is driven by women. We find no evidence that locus of control influences optimism and confidence about the return to stated effort, or that it operates through an illusion of control.
Keywords: D83; D87; D91; 330; locus of control; preference for agency; decision-making; beliefs; optimism; confidence; illusion of control